Analisis Pengaruh Kebijakan Produk Dalam Hukum Perdagangan Internasional Terhadap Implementasi Skala Bisnis Internasional - Panca Syahputra; Hendra Ibrahim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Not all products are well received in all countries. Thus, it is important for foreign companies to make various adjustments to the products offered. Companies must ensure that their products are well received by society and do not conflict with society's culture. If companies fail to adapt their products, there is a possibility that the company will not survive in the long term. In this article the author will explain the influence of product policy in international trade law, the importance of product policy factors that influence international business, and how product policy strategies influence the implementation of international business. The research method used is collecting and processing data from various sources, including online journals that are relevant to the topic of discussion.